PENGARUH PROBLEM BASED LEARNING BERBANTUAN PORTOFOLIO TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Sari, Diah Permata; Koryati, Dewi (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2025)
Education is very important to develop human resources and the progress of a nation and country. Where learning outcomes are one of the benchmarks in achieving learning goals and self-abilities. This study aims to prove the impact of the influence of the problem based learning model on learning outcomes in the subject of economics of students at SMA Negeri 2 Indralaya Utara. This study was conducted on students of class XI Phase F using the Pre Experimental Design design with the form of One Group Pretest-Posttest. The method used in this study is through a test instrument with a statistical analysis technique in the form of a Paired Sample t-test or paired t-test. The results obtained from this study are the value of t_{count\ }> t_{table} or 12.79> 1.714 where it means that Ha is accepted and Ho is rejected. So it can be concluded that there is an influence of the application of the Problem Based Learning Model Assisted by Portfolios on the Economic Learning Outcomes of Students at SMA Negeri 2 Indralaya Utara. The researcher suggests that in the future educators can use more interactive learning models and utilize portfolios in the learning process so that students' knowledge and learning styles are broader.